Performance of commercial mycoplasma hyopneumoniae serum enzyme-linked immunosorbent assays under experimental and field conditions - Silva, Ana Paula S. Poeta; Magtoto, Ronaldo L.; Almeida, Henrique M. Souza [UNESP]; McDaniel, Aric; Magtoto, Precy D.; Derscheid, Rachel J.; Merodio, Maria M.; Ferreyra, Franco S. Matias; Gatto, Igor R.H. [UNESP]; Baum, David H.; Clavijo, Maria J.; Arruda, Bailey L.; et al. (American Society for Microbiology, 2020)
Mycoplasma hyopneumoniae is an economically significant pathogen of swine. M. hyopneumoniae serum antibody detection via commercial enzyme-linked immunosorbent assays (ELISAs) is widely used for routine surveillance in commercial swine production systems. Samples from two studies were used to evaluate assay performance. In study 1, 6 commercial M. hyopneumoniae ELISAs were compared using serum samples from 8-week-old cesarean-derived, colostrum-deprived (CDCD) pigs allocated to the following 5 inoculation groups of 10 pigs each: (i) negative control, (ii) Mycoplasma flocculare (strain 27399), (iii) Mycoplasma hyorhinis (strain 38983), (iv) Mycoplasma hyosynoviae (strain 34428), and (v) M. hyopneumoniae (strain 232). Weekly serum and daily oral fluid samples were collected through 56 days postinoculation (dpi). The true status of pigs was established by PCR testing on oral fluids samples over the course of the observation period. Analysis of ELISA performance at various cutoffs found that the manufacturers' recommended cutoffs were diagnostically specific, i.e., produced no false positives, with the exceptions of 2 ELISAs. An analysis based on overall misclassification error rates found that 4 ELISAs performed similarly, although one assay produced more false positives. In study 2, the 3 best-performing ELISAs from study 1 were compared using serum samples generated under field conditions. Ten 8-week-old pigs were intratracheally inoculated with M. hyopneumoniae. Matched serum and tracheal samples (to establish the true pig M. hyopneumoniae status) were collected at 7- to 14-day intervals through 98 dpi. Analyses of sensitivity and specificity showed similar performance among these 3 ELISAs. Overall, this study provides an assessment of the performance of current M. hyopneumoniae ELISAs and an understanding of their use in surveillance.
Keywords: Cross-reactivity; ELISA; Misclassification error rate; Mycoplasma flocculare; Mycoplasma hyopneumoniae; Mycoplasma hyorhinis; Mycoplasma hyosynoviae; Oral fluids; Test performance